The Effect of Service Quality, Digitalization and Socialization on Motor Vehicle Taxpayer Compliance: Case Study at Samsat Karawang - Cecep Sulaeman; Dedi Mulyadi; Yanti (Borong Newinera Publisher, 2024)
The aim of this research is to evaluate the influence between tax services, tax socialization and digitalization in SAMSAT Karawang district. The independent variables are tax services, tax socialization, and tax digitalization with the related variable, namely motor vehicle taxpayer compliance. The main data will be collected through distributing online questionnaires using Google forms. The sample size of 100 (one hundred) respondents from the Karawang Regency area was used to assess the questionnaire using a Likert scale, and had used the SAPAWARGA application to manage their tax documents and motor vehicle tax payments. The research results show that tax services and the implementation of digitalization have a positive effect on vehicle tax compliance in Karawang district. Meanwhile, tax socialization has a negative impact on the implementation of taxpayer compliance in Karawang district. This research shows that digital applications must be improved and introduced more widely to the public because implementing the SAPAWARGA application can also increase taxpayer compliance. This is because a lack of understanding can lead to non-compliance or attempts to avoid taxes. By encouraging tax socialization that emphasizes fairness, profits, tax benefits and transparency, the government can increase tax compliance and reduce the tax gap between the target and actual amounts in SAMSAT Karawang Regency.